Performance of soybean (Glycine max) intercropped with different cereals under varying levels of nitrogen - LAYEK, J; SHIVAKUMAR, B G; RANA, D S; MUNDA, S; K, LAKSHMAN; A S, PANWAR; DAS, A; I, RAMKRUSHNA G (The Indian Journal of Agricultural Sciences, 2015)
A field experiment conducted during 2009 and 2010 at the research farm of the Indian Agricultural Research Institute, New Delhi to study the performance of soybean as influenced by the intercropping of cereals, viz. maize (Zea mays L.), sorghum [Sorghum bicolor (L.) Moench.] and pearl millet (Pennisetum glaucum L.) with 0, 50, 75 and 100% of their respective recommended dose of N (RDN) levels. In all 12 intercropping systems in 2:1 ratio of soybean+ maize, soybean+sorghum and soybean+pearl millet with 4 levels of RDN to cereal component crops along with sole soybean were carried out in a randomized block designand replicated thrice. The performance of soybean was greatly influenced by the intercrops as well as N levels. The sole crop of soybean recorded higher number of branches, drymatter accumulation, root biomass; leaf area index, crop growth rate and relative growth rate as compared to soybean grown in intercropping systems. Likewise the yield attributes, yield and harvest index were also higher with sole soybean. Among the intercropping systems, soybean+pearl millet had greater negative impact on performance of soybean as compared to soybean+maize and soybean+sorghum system. The increase in N levels to cereal crops in intercropping systems showed negative impact on the growth and yield attributes, and yield of soybean. The 100% RDN to intercropped cereals had the highest negative effect while the control had the least. The highest gross returns, net returns, B: C ratio and soybean equivalent yield (SEY) were observed under soybean+maize intercropping system along with 100% RDN to intercropped maize in both the years of experimentation. Among the intercropping systems, soybean+maize intercropping systems recorded higher returns and SEY than others.